Art, Philosophy, and Ideology : Writings on Aesthetics and Visual Culture from the Avantgarde to Postsocialism - Erjavec, Aleš, (Religious Studies, Theology and Philosophy E-Books Online, Collection 2024., 2024)
This volume presents a selection of aesthetic and art theoretical writings by the internationally renowned philosopher Aleš Erjavec from the 1990s to the present. Erjavec was an active participant in the artistic revolt in Slovenia throughout the 1980 and became one of the most notable international theorists of late- and post-socialist developments in art. His work also extended to new, emergent forms of contemporary art and visual culture in global art and culture networks. The diverse contexts and artists with which he has engaged gives him a unique critical perspective on major debates in philosophical aesthetics and art theory.